Sufism streamology in the Indian subcontinent and its peaceful coexistence with other religions - Seyed Mehdi Taheri (Kom: Časopis za Religijske Nauke)
The Indian subcontinent is considered one of the five ancient civilizations in the world and the inheritor of a magnificent and diverse culture. India, as the largest country in this subcontinent, is considered the seventh largest country in the world. Due to its strategic importance, this region has always been favored by people from other parts of the world. Regarding the relationship of other nations, races and religions with the people of the Indian subcontinent, they were able to influence the life and culture of the region. One of the distinctive features of this region is the existence of different religions and religious sects, among which Hinduism, Buddhism and Islam are the most important religions of the region. The mentioned religions have many sects in the region, and one of the important Islamic sects is Sufism, which has established a positive interaction with other religions by becoming indigenous in the subcontinent and peacefully coexisting. In this article, after discussing the potentials and capacities of the subcontinent region, the author tries to investigate issues such as the importance of peaceful coexistence in Islam, interring in Islam and Sufism to the subcontinent, different sects of Sufism and its peaceful coexistence with other religions. In this regard, the author believes that Sufism was able to influence Hindu seekers through familiarity with philosophical works, the type of worldview and interaction with mystics and also through the peaceful coexistence emphasized by Islam. By taking advantage of good morals, decent behavior and the call to philanthropy derived from Islam, not only did they gain great influence among the common people, but beyond that, throughout history, they were able to attract the devotion of kings and gain a lot of power in the courts of some rulers of India.